BEBAN PERAWATAN, KESIAPAN MERAWAT, DAN KECEMASAN PADA FAMILY CAREGIVER ANAK DENGAN KANKER DI INDONESIA - Harahap, Nurlelasari; Waluyo, Agung; Nuraini, Tuti; Sutarni , Nani (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
ABSTRACT Background: Family caregivers (FCs) of children with cancer experience various psychological stresses. Objective: This study aims to identify the relationship between burden of care and readiness to care on family caregiver anxiety of children with cancer. Methods: The design in this study is correlative analytic with a cross sectional approach. We recruited 127 study subjects from the inpatient and outpatient ward of the National Cancer Centre, Jakarta from March to April 2023 using purposive sampling technique. Anxiety and factors affecting the psychological distress of family caregivers of children with cancer were identified with the Generalised Anxiety Disorder-7 (GAD-7), Zarit Burden Interview (ZBI) and Preparedness for Caregiving Scale (PCS) instruments. The data from this study were analyzed using the chi-square test and binary logistic regression. Results: Of the 132 family caregivers recruited for this study in the initial phase, 127 family caregivers completed the research questionnaire where the majority were female, aged between 18-45 years old, graduated from secondary education, had more than equal income, caring for children with high risk, were in outpatient or paediatric care, experienced mild care burden, said they were not prepared to provide care to a child with cancer, and experienced mild anxiety. Family caregiver anxiety levels tended to be significantly influenced by age (18-45 years) (p=0.004), cancer category (p=0.018) and burden of care (0.001). Conclusion: the heavier the burden of care and the unpreparedness of family caregivers in providing care to children with cancer, the level of anxiety will increase. Suggestion: there is a need to design and target psychosocial interventions to reduce the burden of care, increase care readiness which can reduce family caregiver anxiety levels.